Logjam attenuation of annual sediment waves in eolian-fluvial environments, North Park, Colorado - Grabowski, Julia, author; Wohl, Ellen, advisor; McGrath, Daniel, committee member; Morrison, Ryan, committee member (Colorado State University. Libraries, 2020)
Sediment waves, a term that describes the fluvial transport of a discrete sediment influx, have long been studied in regard to channel response to infrequent, catastrophic events, such as mass movements or dam removal. However, few researchers have studied (1) the potential presence of sediment waves of annual or sub-annual scale in mixed eolian-fluvial geomorphic environments or (2) the role of large wood in sediment wave dispersal. This study addresses both topics through observations of North Sand Creek and East Sand Creek, which flow alongside the active sand dunes of North Sand Hills and East Sand Hills, respectively, in North Park, Colorado. The creeks experience similar seasonal, asynchronous cycles of eolian influx and fluvial transport, although North Sand Creek likely receives a greater volume of eolian sand due to intensive Off-Highway Vehicle (OHV) recreation on the North Sand Hills dunefield. Linear spectral unmixing of Landsat imagery from 1984-2019 is used to determine whether OHV recreation has resulted in vegetation loss, typically associated with elevated eolian flux, on North Sand Hills. Repeat photography and repeat measurement of terrace-like structures are used to determine whether each creek experiences a sediment wave, and repeat measurement of logjam sand wedge volume is used to examine changes in sand storage associated with logjams over time. Results indicate that North Sand Hills hast lost vegetative cover in areas not fenced-off to OHV users at a rate of ~800 m2/year, and that North Sand Creek experiences a highly translative sediment wave that is attenuated by logjams. East Sand Hills, on the other hand, has gained vegetative cover throughout the dunefield, and East Sand Creek does not experience a sediment wave. The sediment wave at North Sand Creek translates rapidly through the area of channel outside of the logjam backwater and translates more slowly through logjam backwater areas—principally through reduction in the length of logjam sand wedges, rather than reduction in depth.
Zip file contains supplementary videos, no sound.
Keywords: OHV impact; spectral unmixing; sediment wave; eolian-fluvial